Current theory and practice of assessment centers: The importance of trait activation - LIEVENS, Filip (Institutional Knowledge at Singapore Management University, 2008)
Assessment centers have always had a strong link with practice. This link is so strong that the theoretical basis of the workings of an assessment center is sometimes questioned. In this chapter, we posit that trait activation theory (Tett and Burnett 2003) might be fruitfully used to explain how job-relevant candidate behavior is elicited and rated in assessment centers. Trait activation theory is a recent theory that focuses on the person–situation interaction to explain behavior based on responses to trait-relevant cues found in situations. These observable responses serve as the basis for behavioral ratings on dimensions used in a variety of assessments such as performance appraisal, interviews, but also assessment centers.